(untitled) (Raparin Journal of Humanities (RJH), 2026)
Climatic water balance indicates the differences between excess and deficiency of water; in this way we can get accurate and scientific data. It is used as a basis for designing water absorption plans and treating water deficiency. The significance of the study is that we are getting accurate and scientific data about monthly water quantity in the study area, with the aim of reducing deficiency of water in the dry season. The main goal is getting accurate data about excess and deficiency of water in all months of the year. Also creating a map for climate elements and climatic water balance in the study area. Each of the methods of comparative and analysis methods are used for analysis of climate elements data showing on the map in the study area, with a specific equation for climatic water balance, and shows excess and deficiency of water in the study area. We have got some results by using each of the Efanov and Thornthwaite equations in the study area. From (11-4) months for 6 months, water balances are in excess in all weather stations; in contrast, from (5-10) for 6 months, we have water deficiency in all weather stations. Also, in an average year, regarding climatic water balance, the water deficiency in the study area is between (1306-)-(1580.3-) mm and is divided into 4 zones from south to north towards water deficiency decrease, so that the minimum water deficiency line between (-1306) – (-1374.5) mm is located in the north of the study area and the maximum water deficit is between (-1511.7) – (-1580.3) mm and is located in the south of the study area.